Peningkatan pengetahuan aspek perpajakan dan kualitas pengelolaan produk pada kelompok UMKM - Yeney Widya Prihatiningtias; Sri Palupi Prabandari; Devi Nur Cahaya; Areta Widya Kusumadewi; Octadila Laily Anggraeni; Karimatun Nisa’; Ainul Rizkiyah; Fajar Hafidh Arasy (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
This community service activity is carried out to provide training and assistance to MSME groups that are members of the KSU Amangtiwi Malang City. This activity is carried out in relation to aspects of taxation and quality of product management, including aspects of trademark registration, food production certificates, foodstuff registration, halal label registration, and marketing methods. The hope is that these MSME players can stand up to their position in managing their products to enter the international market, as well as being orderly and obedient in tax administration. The method of implementing this activity combines online and offline to minimize the number of people gathering during the Covid-19 pandemi. The stages of the activities carried out were socialized and FGD (Focus Group Discussion) to identify initial needs; training in product management and marketing; assistance in trademark management; as well as training and assistance for MSME taxation and accounting. The activity was completed well and smoothly so that the participants were satisfied and This activity is assisted by this activity. Participants gain a better understanding of tax obligations and reporting procedures as well as an understanding of product management which includes trademark registration, SPP-IRT, BPOM and halal labels. Therefore, a follow-up program is needed so that assistance can be carried out inventively so that the participants are independent in managing their business.